ANALYSIS OF QUALITY IMPROVEMENT TO IMPROVE PRODUCTIVITY OF PISTON RING PVD WITH SIX SIGMA (DMAIC) APPROACH - Astuti Widi Rahayu, Ade; N. , Neni Triana; Komarudin, Udin (International Journal of Psychosocial Rehabilitation, 2020)
PT. NT Piston Ring Indonesia is a manufacturing company that engages in the automotive sector especially in motor vehicle engine components. One of the products produced is Piston Ring. The problem facing the company today is how to improve and maintain product quality in order to minimize defective products that can cause harm to companies, especially on a large scale. This study uses the Six Sigma method as an improvement approach that aims to find and eliminate the causes of defective products that often occur. The stages used are the stages of DMAIC (Define, Measure, Analyze, Improve and Control). At the define stage it is known that there are 15 types of CTQ on the GD-HIGH S. Piston Ring PVD product model. Then at the measure stage it is known that the highest pareto defect diagram is on the type of hakuri defect with a total defect reaching 32.1% with attribute data using a control chart p for which most data are still out of control. DPMO value was 21.888 and sigma value was 3.52. Then proceed to the analysis phase for analysis using a fishbone diagram and FMEA process. Now we know the root cause corrective suggestions made to improve and reduce the number of defects that occur in the product Piston Ring PVD-HIGH GD models S.